Dynamics of ions during development of parametric instability of langmuir waves - Belkin, E.V.; Kirichok, A.V.; Kuklin, V.M.; Pryjmak, A.V.; Zagorodny, A.G. (Вопросы атомной науки и техники, 2013)
Nonlinear regimes of one-dimensional parametric instabilities of long-wave plasma waves are considered for the cases when the average field energy density is less (Zakharov’s model) or greater (Silin’s model) than the plasma thermal energy. The process of generation of short-wave plasma waves and perturbations of ion density is found to be similar in both cases. It is shown that the ion energy after the instability is saturated proves to be of the order of the ratio of linear growth rate to the frequency in the case when the initial field energy exceeds the plasma thermal energy. In the opposite case of hot plasma, the ions acquire a part of initial field energy equal to the ratio of initial field energy to the plasma thermal energy. The trajectory crossing of ions in the vicinity of density cavities is a reason of instability quenching in both cases. Розглянуто нелінійні режими розвитку одновимірних параметричних нестійкостей довгохвильових ленгмюрівських хвиль у випадках, коли енергія поля менша (модель Захарова) і більша (модель Сіліна) за теплову енергію плазми. Процес генерації короткохвильового спектра плазмових хвиль і збурень іонної густини виявляється подібним в обох моделях опису параметричних нестійкостей. Показано, що енергія іонів при насиченні нестійкостей виявляється дорівнює за порядком відношенню лінійного інкремента до частоти у випадку, коли початкова енергія поля помітно перевищує теплову енергію плазми. В умовах гарячої плазми іонам передається частка енергії, що дорівнює половині відношення початкової енергії поля до теплової енергії плазми. Перетин траєкторій іонів поблизу каверн густини є причиною зриву нестійкості в обох випадках. Рассмотрены нелинейные режимы развития одномерных параметрических неустойчивостей длинноволновых ленгмюровских волн в случаях, когда энергия поля меньше (модель Захарова) и больше (модель Силина) тепловой энергии плазмы. Процесс генерации коротковолнового спектра плазменных волн и возмущений ионной плотности оказывается подобным в обеих моделях описания параметрических неустойчивостей. Показано, что энергия ионов при насыщении неустойчивостей оказывается порядка отношения линейного инкремента к частоте в случае, когда начальная энергия поля заметно превышает тепловую энергию плазмы. В условиях горячей плазмы ионам передается доля энергии, равная половине отношения начальной энергии поля к тепловой энергии плазмы. Пересечение траекторий ионов вблизи каверн плотности является причиной срыва неустойчивости в обоих случаях.